Discovering Emotional Intelligence. - Emerald Group Publishing (Emerald Group Publishing, 2005)
It has been claimed that - astonishingly - almost 90 percent of success in leadership positions is attributable to Emotional Intelligence (EI). According to the Emotional Intelligence Homepage, EI has been around a lot longer than you may think. The first traces of EI date back to a graduate student paper written in 1985 and further work carried out by two university professors in 1990. Since then Emotional Intelligence has gradually grown in popularity and in 1995 even made the cover of Time Magazine! Today EI has become one of the most hotly debated business buzzwords in America. According to a paper by Cary Cherniss presented on the Consortium for Research on Emotional Intelligence in Organizations website, an article on the subject published in Harvard Business Review in 1998 attracted a higher percentage of readers than any other article published in the last 40 years. But despite the media exposure and clear signs of popularity, many argue that EI still remains a poorly understood phenomenon in today's workplace. So what exactly is it? The two university professors who coined the term in 1990 describe Emotional Intelligence as: "A form of social intelligence that involves the ability to monitor one's own and others' feelings and emotions, to discriminate among them, and to use this information to guide one's thinking and action." This is clearly a wide ranging definition with plenty of scope for investigation. And our Briefing aims to do just that!